Septins restrict inflammation and protect zebrafish larvae from Shigella infection. - Maria J Mazon-Moya; Alexandra R Willis; Vincenzo Torraca; Laurent Boucontet; Avinash R Shenoy; Emma Colucci-Guyon; Serge Mostowy (PLoS Pathogens)
Shigella flexneri, a Gram-negative enteroinvasive pathogen, causes inflammatory destruction of the human intestinal epithelium. Infection by S. flexneri has been well-studied in vitro and is a paradigm for bacterial interactions with the host immune system. Recent work has revealed that components of the cytoskeleton have important functions in innate immunity and inflammation control. Septins, highly conserved cytoskeletal proteins, have emerged as key players in innate immunity to bacterial infection, yet septin function in vivo is poorly understood. Here, we use S. flexneri infection of zebrafish (Danio rerio) larvae to study in vivo the role of septins in inflammation and infection control. We found that depletion of Sept15 or Sept7b, zebrafish orthologs of human SEPT7, significantly increased host susceptibility to bacterial infection. Live-cell imaging of Sept15-depleted larvae revealed increasing bacterial burdens and a failure of neutrophils to control infection. Strikingly, Sept15-depleted larvae present significantly increased activity of Caspase-1 and more cell death upon S. flexneri infection. Dampening of the inflammatory response with anakinra, an antagonist of interleukin-1 receptor (IL-1R), counteracts Sept15 deficiency in vivo by protecting zebrafish from hyper-inflammation and S. flexneri infection. These findings highlight a new role for septins in host defence against bacterial infection, and suggest that septin dysfunction may be an underlying factor in cases of hyper-inflammation.